National Innovation System and an Approach to Innovation Activities at the Scale of an Economic Sector: Some Theoretical Foundations - Ngoc Ca, Tran; Thanh Tung, Dang (VNU Journal of Science: Policy and Management Studies, 2023)
Innovation is one of the important factors for rapid and sustainable economic and social development in an internationally competitive environment. Identifying and analyzing the national innovation system is a necessary need, moving towards building policy solutions to support Vietnam's national innovation system. However, at the scale and level of an economic industry, this connotation can and should be developed and applied according to the industry innovation system approach. Keywords: National innovation system, sectoral innovation system, emerging innovation system, fragmented (dual) innovation system.